The influence of air pollution on disease and related health problems in Northern Thailand - Sakesun Thongtip; Piyavadee Srivichai; Narong Chaitiang; Kraichat Tantrakarnapa (Penerbit Universiti Kebangsaan Malaysia, 2022)
Air pollution is a significant health risk factor. Long-term exposure to ambient air pollution has a significant impact on chronic respiratory illnesses and diseases related to health problems. The aim of this study was to investigate the association between air pollution, respiratory diseases and diseases related to health in Northern Thailand. The daily mean concentrations of PM10 and PM2.5, including meteorological condition data from 2015 to 2020, were measured and recorded by Pollution Control Department (PCD), Ministry of Natural Resources and Environment, Thailand. The daily cumulative number of respiratory diseases and related health problems data from 2015 to 2020 was measured and recorded by Information and Communication Technology Centre, Ministry of Public Health, Thailand. The daily mean concentrations of PM10 and PM2.5 were positively associated with CO, NO2, SO2, O3, circulatory system (I00-I99), respiratory system (J00-J99.8), eye (H10-H19.8), rash and other nonspecific skin eruption (R21), and neoplasms (C00-D48). After adjusting for confounding factors, the multiple linear regression analysis revealed that the escalating daily mean PM10 concentrations were connected to the increasing daily mean PM2.5 concentrations. This indicates that providing health education programmes and pollution protection, as well as policymakers and legislation, is required for better health.